Pulsed GMAW-based WAAM–Influence of droplet detachment mode on the geometry and mechanical properties of 308 L stainless steel - R.F. Rezende; A.R. Arias; E.J. Lima, II; F.G.F. Coelho (Journal of Advanced Joining Processes)
This study aimed to introduce pulsed gas metal arc welding (GMAW)-based wire arc additive manufacturing (WAAM) for the deposition of 308 L stainless steel. Then, the influence of the different droplet detachment modes on the geometric characteristics and mechanical properties of the deposited metal were analyzed. The detachment modes of one drop per multiple pulses (ODMP), one drop per pulse (ODPP), and multiple drops per pulse (MDPP) were analyzed. The experiments were performed by depositing preforms using 308 L stainless steel wire with a diameter of 1.0 mm on a 316 L stainless steel substrate. Characterization of the droplet detachment modes was performed using a high-speed camera and data acquisition system. Geometric analysis of the preforms was performed by photogrammetry. A greater heat input was observed in the ODMP mode. The MDPP and ODPP modes produced thinner preforms with a better surface finish. In addition, the MDPP mode generated better results in the manufactured preforms, with lower hardness and higher tensile strength. However, the ODMP mode led to relatively poorer results, with wider walls, greater surface waviness, and lower tensile strength. The results of this research are expected to provide technical and scientific support for the development of additive manufacturing by arc deposition, especially for stainless steel applications.